Interaction effects of sedentary behavior and depression on MAFLD in NHANES 2017–2020 and 2021–2023 - Wuqian Zhang; Yujing Wang; Qunyou Cong; Xiaoshun Tang; Zhe Wang; Zhirong Wang (PLoS ONE, 2026)
Background Metabolic-associated fatty liver disease (MAFLD), a disease closely associated with metabolic abnormalities (e.g., insulin resistance, dyslipidemia, elevated blood glucose, and obesity), has become a global public health challenge. This study explored the independent associations between sedentary behavior and depressive symptoms with MAFLD and analyzed the potential interactions between these two factors and the risk of MAFLD occurrence. Methods This cross-sectional study is based on data from two cycles of the National Health and Nutrition Examination Survey (NHANES) from 2017 ~ 2020 and 2021 ~ 2023 and analyzes the relationships among depressive symptoms, sedentary behavior, potential confounding factors, and MAFLD. A multivariate logistic regression model was used in the present study, and different subgroups of sedentary behavior were analyzed to assess the associations among sedentary behavior, depression and MAFLD. In addition, the presence of additive interactions among these variables was assessed by calculating the relative excess risk due to interaction (RERI), attributable proportion due to interaction (AP), and synergy index (S). Results A total of 10,612 participants were included in this study (weighted sample size of 183,231,593), of whom 4,501 (weighted proportion of 42%) had MAFLD. Compared with participants with less daily sedentary time, those with more sedentary time had a greater risk of MAFLD (OR = 1.33, 95% CI: 1.08 ~ 1.64). We also found that, compared with individuals without depressive symptoms, individuals with depressive symptoms were significantly associated with an increased risk of MAFLD (OR = 1.26, 95% CI: 1.03 ~ 1.54). Furthermore, sedentary behavior significantly interacted with depression in overweight individuals, affecting the risk of MAFLD (relative excess risk (RERI) = 0.684, 95% CI: 0.312 ~ 1.057; attributable proportion (AP) = 0.360, 95% CI: 0.323 ~ 0.397; synergy index (S) = 1.623, 95% CI: 1.177 ~ 2.070). Poisson regression with 90% CI confirmed this interaction (RERI = 0.318, 90% CI: 0.036 ~ 0.600; AP = 0.223, 90% CI: 0.182 ~ 0.263; S=1.310, 90% CI: 1.000 ~ 1.620). Conclusion Sedentary behavior and depression have a significant synergistic effect on MAFLD in overweight individuals. Therefore, improving individuals’ psychological health status and reducing sedentary time may have positive effects on the prevention and treatment of MAFLD.